Social Perception and Stigma: Creating an Inclusive and Equal Society - Hardyansah, Rommy; Saputra, Rio; Negara, Dharma Setiawan (Journal of Social Science Studies, 2021)
Misperceptions of certain groups, such as minority groups or people with disabilities, often form stigmas that lead to discrimination and marginalization. This social stigma not only impacts the stigmatized individuals but also affects their social and psychological well-being and creates inequalities in society. This research examines how social misperceptions contribute to the formation of stigma and its impact on individuals and social stability. A comprehensive approach is needed to reduce stigma, including awareness raising through education, promotion of empathy, inter-group interaction, as well as affirmative policies that support social inclusion. The media also has an important role to play in changing public perceptions by portraying more positive and accurate representations of stigmatized groups. In addition, an inclusive education system has the potential to reduce discrimination by creating spaces to understand and accept differences. The research also highlights the importance of periodic evaluation of implemented policies and interventions to ensure the sustainability of social change. Based on the results of this study, it is recommended that these efforts continue to be strengthened by involving all levels of society to create a more inclusive and equitable environment.